Further studies on lethal threat of damaged concrete debris due to accidental explosions - Cham, Jun Bi (2015)
Past research studies explored the various potential threats of damaged concrete debris, and concluded 79 Joules of kinetic energy as lethal. Within a controlled experimental environment, the shoot against a soil bed was conducted while capturing the multiple trajectories projected, and hence the lethality curve was derived. This report is an extension of these previous studies, where preliminary drop tests were conducted against concrete slabs to stimulate scenarios of actual accidental explosions in an explosive storage place. This report in particular, will focus on the characterization of the breakup and energy relations of the concrete debris, while the experimental procedures would be covered on the report of the writer’s research partner (Yon, J., 2015). Based on the various results obtained, concrete debris does not define a higher lethal zone concluded by past research, but would cause significant density ricochets, inflicting severe injuries onto any personnel within proximity.